2013
DOI: 10.1016/j.exphem.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Hoxa9 overexpression predisposes to the development of lymphoid but not myeloid leukemia

Abstract: Hoxa9 is expressed in hematopoietic stem and progenitor cells although this expression is usually diminished as these cells undergo differentiation. In addition, aberrant expression of Hoxa9 is strongly associated with both T-cell and myeloid leukemia in mice and humans. Despite this strong association, enforced expression of Hoxa9 in murine bone marrow or thymus has only shown a modest ability to transform cells. To investigate this question, we used Vav regulatory elements to generate a transgenic mouse that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…HOXA genes are dysregulated in leukemias 46 , 47 and HOXA9 has been previously implicated in mouse foetal HSC self-renewal 32 , 48 . Knockout mice for other Hoxa genes have not revealed strong HSC phenotypes, presumably due to compensation by other Hox genes 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…HOXA genes are dysregulated in leukemias 46 , 47 and HOXA9 has been previously implicated in mouse foetal HSC self-renewal 32 , 48 . Knockout mice for other Hoxa genes have not revealed strong HSC phenotypes, presumably due to compensation by other Hox genes 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of HOXA9 induces apoptosis in human MLL-positive AML lines, thus signifying its role in repressing apoptosis pathways [12], whereas downregulation of MEIS1 in MLL-rearranged leukemia cell lines results in decreased proliferation and transcriptional repression of cell-cycle entry-related genes [13]. In addition, HOXA9 overexpression has been involved in a subset of lymphoid malignancies, most predominantly precursor T-cell lymphoblastic leukemia/ lymphoma (pre-T LBL) [14,15]. This overexpression is often, but not invariably, accompanied by upregulation of MEIS1, mostly in acute lymphocytic leukemias (ALLs) bearing MLL translocations and to a lesser extent in T-cell ALL characterized by other gene fusions [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%